The Image of Mammy in Lynn Nottage’s by the Way, Meet Vera Stark - Snoor Ismael Mahmood; Saman Hussein Omer (Zanco Journal of Humanity Sciences)
Certain dominant images are created and disseminated through various modes of communication to define black women in the United States. The purpose of this research is to examine the Mammy image in Lynn Nottag's play, By the Way, Meet Vera Stark. It tends to analyze the constructed image of black womanhood in America's mainstream culture by examining the stereotypical depiction of the central character, Vera, and her role in the Hollywood film. The image is analyzed from the perspective of black feminist theories. Through contextual clues and context-based analysis, the systematic construction of the image in a white-dominated culture is revealed. The study's findings conclude that racist images are created to determine and justify black women's subordinate status in society. The author defies the image as an inhumane misrepresentation of black womanhood and hopes for radical illumination of the distorted image of black women and its ideological legacy that black women can only be servants.